The World of Regions or Regions of the World. Book review of ‘Asymmetries of Regional Integration Projects in the 21st Century’ - E. V. Khakhalkina (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2020)
The book under review is a multiauthored book ‘Asymmetries of regional integration projects in the 21st century’ published in 2018. The book assesses both the key contemporary integration projects and their role in a global political system. The review provides a detailed description of the contents of the book. The reviewer emphasizes that the analysis of individual integration projects is preceded by a detailed and informative overview of theoretical basis for studies on integration. The authors examine these issues through the prism of contemporary attempts by the academic community to define the existing world order. Each integration project is considered as a product of specific historical, cultural, political and socio-economic features of a particular state or a group of states. At the same time, fundamental questions of the role of regions in the future global order, as well as of proportion between stabilizing and destabilizing factors and practices within each of them remain open. The review focuses on the authors’ assessments of the current state and prospects for the development of the European Union. In this regard the reviewer examines the authors’ views on the concepts of ‘multiculturalism’ and ‘intercultural dialogue’. Finally, the reviewer pays special attention to the authors’ assessments of the Russian projects of Eurasian integration and of the prospects for their interlinking with the European and Chinese initiatives. The reviewer concludes that this book sets out new directions for research of both the regional integration projects and their role in the global world order, and of interaction between individual countries and groups of states.